2014
DOI: 10.2174/1871527313666140618105404
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Citrus reticulata in Scopolamine-Induced Dementia Oxidative Stress in Rats

Abstract: The purpose of the study was to evaluate the potential effects of Citrus reticulate (mandarin) peel methanolic extract (MPME) on memory dysfunction in rats. Memory impairment was produced by scopolamine (1.4 mg/kg, intraperitoneally injected). Brain acetylcholinesterase enzyme (AChE) activity was measured to assess the central cholinergic activity. This study also investigated the effect of scopolamine on norepinephrine, dopamine and serotonin content in rat hippocampus, striatum and cerebral cortex. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Nevertheless, El‐Khadragy et al. () reported significant alterations in brain monoamines in rats administered 1.4 mg/kg SCOP. Thus, we hypothesize that the significant reduction in MAO activity induced by SCOP in this study could be as a result of the higher dose used (2 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, El‐Khadragy et al. () reported significant alterations in brain monoamines in rats administered 1.4 mg/kg SCOP. Thus, we hypothesize that the significant reduction in MAO activity induced by SCOP in this study could be as a result of the higher dose used (2 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that previous reports show no significant effect of SCOP on brain MAO activity (Bihaqi, Singh, & Tiwari, 2011;Liu et al, 2017;Rubio et al, 2017); we, however, observed that these studies reported administration of 1 mg/kg SCOP. Nevertheless, El-Khadragy et al (2014) reported significant alterations in brain monoamines in rats administered 1.4 mg/kg SCOP. Thus, we hypothesize that the significant reduction in MAO activity induced by SCOP in this study could be as a result of the higher dose used (2 mg/kg).…”
Section: Re Sultmentioning
confidence: 98%
See 2 more Smart Citations
“…Increased concentration of acetylcholine leads to improve the communication between the nerve cells that use acetylcholine as a neurotransmitter, which may in turn temporarily improve or stabilize the symptoms of Alzheimer's disease [13-14]. This class of medications may be used for three years, possibly longer.…”
Section: Current Anti-alzheimer's Treatmentmentioning
confidence: 99%